Pengaruh Pelarut Etanol 70% Dan Metanol Terhadap Kadar Flavonoid Total Ekstrak Daun Sirsak (Annona muricata Linn): Pengaruh Pelarut Etanol 70% Dan Metanol Terhadap Kadar Flavonoid Total Ekstrak Daun Sirsak (Annona muricata Linn) - Kunti Nastiti; Nurul Hidayah; Juliance Yolanda Putri (LPPM Universitas Sari Mulia, 2023)
Background: Annona muricata leaf are empirically used to treat a wide variety of diseases. One of the potentials of leaf as antioxidants because they contain flavonoid compounds. This study used a polar solvent, ethanol 70% and methanol to extract flavonoid compounds in leaf, the use of different types of solvents will affect the total flavonoid levels produced. Objective: Knowing the effect of differences in the type of solvent ethanol 70% and methanol on the total flavonoid levels of leaves and qualitative detection of flavonoid compounds. Methods: The study used a pre-experimental method, making Annona muricata leaf extract using the maceration method by comparing 70% ethanol solvent and methanol then flavonoid compounds were detected qualitatively using color reagents and thin layer chromotreography then determination of flavonoid levels with UV-Vis Spectrophotometry and data analyzed with the One Way Anova test. Results: The results of the qualitative detection test showed positive results of flavonoid compounds and the total flavonoid levels produced by ethanol extract were 70% and methanol were 6.79 mg QE / g and 9.25 mg QE / g. The results of the One Way Anova test analysis showed that the difference in the type of solvent had a significant effect on the total flavonoid levels of Annona muricata leaf extract. Conclusion: Differences in solvent types have a significant effect on the total flavonoid levels of Annona muricata leaf extract with the highest levels produced by methanol solvents of 9.25 mg QE/g.